Creación de una ruta sostenible para deportes de aventura “Los Caminos del Montubio”, entre las provincias de Cotopaxi y Los Ríos, año 2019 - Silva Cruz, Diana Elizabeth (2020)
The creation of the sustainable route for adventure sports between the provinces of Cotopaxi and Los Rios, seeks the interaction of the economy and sustainability of the sectors involved and therefore improve the quality of life of all its inhabitants, for this the research proposes the proposal to create the route for adventure sports, where it involves the municipal authorities and administrators of tourist establishments, due to the demand of the population to generate new sources of economic income and the local development of the areas and thus improve the quality of life Of the inhabitants. This research project was carried out through investigative techniques and methods, which starts from the general to the particular in order to analyze and evaluate with nature and at the same time see the performance within the field to improve tourist diffusion. Being these two provinces of great economic potential and a mandatory crossing point to go to the different parts of the Ecuadorian territory crossing from the coast to the mountains or vice versa, in addition to having a variety of attractions that being exploited in an appropriate way would contribute positively to its economic growth.